Television Industry Dynamics in New Order Era The Effect of Broadcasting Policy Towards News Report - SK, Ishadi (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2012)
Television Industry dynamics in New Order Era is influenced by the broadcasting policy established by the authority. The aim of this research is to explain the effect of the policy towards the television news report and its dynamics in New Order era. This research uses qualitative approach. Data analysis technique used is Critical Discourse Analysis (CDA). The researcher selects RCTI, SCTV, and Indosiar as research objects. The result shows that the authoritative broadcasting policy makes television as a mere government political tool. Indonesia broadcasting system in the New Order era demonstrates centralized broadcasting system throughout Java which, in hierarchy, administratively obeys Jakarta central station. The result, in its development, is that the established policy affects the reportage policy which tends to oppose the ruling power, except for TVRI. Although all television stations are designed from the very beginning as New Order political tool and critical supporter, they often play a role as spoilers against President Soeharto’s policy.